New Lepidocyrtus Bourlet, 1839 taxa from Greece (Collembola: Entomobryidae) - Mateos, Eduardo (Zootaxa, 2011)
Published data on genus Lepidocyrtus from Greece are scarce, being L. ligonorum the most common species in the region. In this paper the analysis of several populations of Lepidocyrtus from four Greek islands has allowed to describe the new species L. juliae sp. nov. and L. barbulus sp. nov. These new taxa were previously described as a color form and chaetotaxic variety of L. lignorum respectively in Greece. Along with other seven European species, the two new described taxa form the "Lepidocyrtus lignorum group", defined by the dorsal macrochaetae formula R 0 R 1 R 2 /00/0101+3 (with or without cephalic macrochaeta So). An identification key has been developed for differentiating all species of this group. With the new described taxa the number of Lepidocyrtus species present in Greece increases to five, and the total European Lepidocyrtus species increases to 29.